Peningkatan Hasil Belajar IPS Melalui Pendekatan Keterampilan Proses Pada Siswa Kelas V SD Negeri 317 Borong Kecamatan Herlang Kabupaten Bulukumba - Abdul Wahid; Muhammad Al Muhajir (STKIP Andi Matappa Pangkep, 2021)
The purpose of the implementation of this study is to improve social studies learning outcomes through the Process Skills approach to grade V SD Negeri317 Borong, Herlang District, Bulukumba Regency. This type of research is classroom action research. This study consisted of 2 cycles. Each cycle consists of 4 stages, namely planning, implementing the action, observing, and reflecting. The subjects in this study were teachers and fifth grade students. From the results of this study it can be concluded that through the process skills approach of social studies learning outcomes in grade V SD Negeri 317 Borong, Herlang District, Bulukumba Regency increased. where in the first cycle showed that the learning outcomes had not been optimal or the students' learning completeness was in the sufficient category, while in the second cycle it had increased in the high category. From the results of this study it can be concluded that through the process skills approach of social studies learning outcomes in grade V SD Negeri 317 Borong, Herlang District, Bulukumba Regency increased. where in the first cycle showed that the learning outcomes had not been optimal or the students' learning completeness was in the sufficient category, while in the second cycle it had increased in the high category.